Ultrafine graphene and preparation method thereof
Through crushing and low-temperature ball milling, step-by-step oxidation and microwave pyrolysis expansion processes, combined with ultrasonic treatment, the problems of complex ultrafine graphene preparation process and low yield in the existing technology are solved, and a rapid and reliable large-scale preparation of high-quality ultrafine graphene is achieved.
Patent Information
- Application Number
- CN202311483652.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-08
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-11-08
AI Technical Summary
The prior art is difficult to quickly, reliably and on a large scale to prepare high-quality ultrafine graphene, and the process is complex and the yield is low.
Ultrafine graphene powder is prepared by crushing and low-temperature ball milling. Through step-by-step oxidation and microwave pyrolysis expansion processes, combined with ultrasonic treatment, the preparation of ultrafine graphene is gradually realized.
The rapid, reliable and large-scale preparation of high-quality ultrafine graphene is achieved, reducing the amount of oxidant used and reaction time, simplifying the process flow, and improving yield and product purity.
Smart Images

Figure CN117383550B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of graphite materials, and in particular to ultrafine graphene and a preparation method thereof. Background Art
[0002] Ultrafine graphene is a graphene material with nanometer thickness, which has many unique properties and broad application prospects. However, the difficulty of its preparation process has an important impact on its application and promotion.
[0003] Due to its extremely thin thickness, ultrafine graphene is softer and more transparent, suitable for applications that require flexibility and transparency, such as flexible electronic devices and transparent electrodes; the relatively small thickness of ultrafine graphene means that it has a larger specific surface area, so it has higher activity and sensitivity in fields such as catalysts and sensors; compared with graphene with larger particle size, ultrafine graphene is generally more biocompatible, so it has more potential in biomedical applications, such as biosensors and drug delivery. However, the preparation of ultrafine graphene usually requires more complex processes and technologies.
[0004] The preparation of ultrafine graphene is not easy for scientific research and engineering applications. The preparation of graphene mainly includes chemical vapor deposition, silicon carbide epitaxial growth, solvothermal method, liquid phase ultrasonic exfoliation, mechanical exfoliation and oxidation exfoliation-reduction. Among them, the first three methods are to synthesize graphene from small molecular hydrocarbons on a suitable substrate, which belongs to the bottom-up method and can obtain high-quality graphene, but these methods have high requirements on the substrate and low yield. The liquid phase ultrasonic exfoliation method is to disperse graphite in an organic solvent (such as N-methylpyrrolidone) or surfactant that matches its surface energy, and use ultrasound for tens to hundreds of hours to destroy the van der Waals force between graphite layers to obtain high-quality few-layer graphene (10 layers). However, due to the strong adsorption residue of the exfoliation agent on the graphene, the physical and chemical properties of the graphene will be affected; in addition, the yield of this method is not high. The oxidation exfoliation-reduction method is to first react graphite with a strong oxidant under strong acid conditions to obtain graphene oxide after oxidation exfoliation; then chemical reduction, high-temperature thermal reduction, electrochemical reduction and other methods are used to remove the oxygen-containing functional groups on the surface of graphene oxide to restore the conjugated structure of graphene, but the reduced graphene oxide obtained still has nanoscale holes or structural defects. In the mechanical exfoliation method, mechanical shear force can cause the graphite sheets to slide laterally between each other to achieve the purpose of exfoliating the graphene sheets; and the impact force generated by the vertical collision between the grinding ball and the graphite can further crush the graphene flakes. However, due to the limited number of functional groups on the graphite surface and its almost inert state, the direct mechanical exfoliation method is not only time-consuming and low in yield, but also difficult to control the thickness and size of the graphene product. However, it is still a challenge to quickly, reliably and large-scale prepare high-quality ultrafine graphene. Summary of the invention
[0005] The present invention is made to solve the above-mentioned problems, and aims to provide an ultrafine graphene and a preparation method thereof, by which high-quality ultrafine graphene can be prepared quickly, reliably and on a large scale.
[0006] A first aspect of the present invention provides a method for preparing ultrafine graphene, the preparation method comprising the following steps:
[0007] 1) Crushing and low temperature ball milling: Crushing and low temperature ball milling of graphite to provide ultrafine graphite powder;
[0008] 2) Stepwise oxidation: mixing oxidant 1 with the ultrafine graphite powder provided in step 1) for pre-oxidation; adding oxidant 2 for primary oxidation; adding intercalation agent for auxiliary oxidation intercalation; adding oxidant 2 for secondary oxidation; filtering to provide material and filter out waste acid;
[0009] 3) Microwave and other treatments: The material provided in step 2) is subjected to microwave treatment to provide expanded graphite powder; the expanded graphite powder is mixed with a solvent, subjected to ultrasonic treatment, filter pressing, and dried to obtain ultrafine graphene.
[0010] Another aspect of the present invention provides an ultrafine graphene, which is prepared by the method described in the first aspect of the present invention.
[0011] Compared with the prior art, the present invention has the following beneficial effects:
[0012] 1. The nanographite powder produced by ball milling has a larger interlayer spacing, a certain increase in scales and a larger specific surface area. The difficulty of high surface energy oxidation is greatly reduced, which reduces the amount of oxidant used and the reaction time;
[0013] 2. The precursor prepared by the step-by-step oxidation and microwave pyrolysis expansion process has a large expansion ratio, that is, a larger interlayer spacing, and a weak interlayer van der Waals force, which is conducive to the exfoliation of graphene. The precursor can be quickly exfoliated into a graphene suspension under ultrasound of relatively low sound intensity.
[0014] 3. The present invention uses microwave pyrolysis to simultaneously reduce and expand graphite oxide, does not require the use of a reducing agent, simplifies the process flow, reduces manufacturing costs and is more environmentally friendly.
[0015] 4. The waste acid produced by filtration has economic value, and the waste acid produced by the initial filtration can be recycled.
[0016] 5. The graphene prepared by the present invention has good dispersion performance and will not undergo irreversible agglomeration. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0018] Hereinafter, embodiments of the specifically disclosed ultrafine graphene and the method for preparing the same are described in detail.
[0019] The present invention is a method for preparing nano-scale ultrafine graphene based on the traditional ball milling method. The graphite is ground at room temperature and low temperature environment. The low temperature environment increases the brittleness of graphite, opens the graphite lattice structure, and promotes the subsequent oxidant penetration oxidation; combined with the secondary oxidation process, the reaction degree is effectively controlled to obtain a larger expansion ratio, ensure the intercalation effect, and make the subsequent peeling more thorough. The ultrafine graphene obtained has a higher purity. The method is simple in process, the prepared nano-scale ultrafine graphite has a higher purity, the amount of oxidant, intercalation agent, etc. used in the process is small, the step-by-step oxidation and microwave expansion process make the graphite layer spacing larger, which is conducive to peeling graphene, shortening the ultrasonic duration, and the number of graphene layers finally obtained is lower; the whole process produces less waste acid, simple operation, safe and efficient, suitable for large-scale industrial production, and has a wide range of industrial application prospects. On this basis, the present invention is completed.
[0020] Preparation method of ultrafine graphene
[0021] The present invention provides a method for preparing ultrafine graphene, the preparation method comprising the following steps:
[0022] 1) Crushing and low temperature ball milling: Crushing and low temperature ball milling of graphite to provide ultrafine graphite powder;
[0023] 2) Stepwise oxidation: mixing oxidant 1 with the ultrafine graphite powder provided in step 1) for pre-oxidation; adding oxidant 2 for primary oxidation; adding intercalation agent for auxiliary oxidation intercalation; adding oxidant 2 for secondary oxidation; filtering to provide material and filter out waste acid;
[0024] 3) Microwave and other treatments: The material provided in step 2) is subjected to microwave treatment to provide expanded graphite powder; the expanded graphite powder is mixed with a solvent, subjected to ultrasonic treatment, filter pressing, and drying to obtain ultrafine graphene.
[0025] In the method for preparing ultrafine graphene provided by the present invention, step 1) is to crush graphite and perform low-temperature ball milling to provide ultrafine graphite powder. Specifically, the graphite is ground, pulped, separated, and dried to provide dried graphite powder, and the dried graphite powder is subjected to low-temperature ball milling to provide ultrafine graphite powder.
[0026] In step 1) of the present invention, graphite: the graphite is flake graphite, which can be high carbon flake graphite. The particle size N of the flake graphite is 100 mesh>N>325 mesh, and it is processed as a raw material. Optionally, the particle size of the flake graphite can be, for example, 100 mesh>N>200 mesh, 300 mesh>N>300 mesh, or 300 mesh>N>325 mesh, etc.
[0027] In step 1) of the present invention, grinding: grinding the graphite using a ball mill.
[0028] The grinding media is selected from high chromium steel balls or zirconium oxide balls.
[0029] The ball-to-material ratio is 11:1-9:1, and can be selected as 11:1-10:1 or 10:1-9:1, etc. The ball-to-material ratio refers to the mass ratio of the grinding medium to the raw material in the ball mill.
[0030] The grinding time is 4 to 5 hours, which can be 4 to 4.5 hours or 4.5 to 5 hours, etc. When the grinding time is controlled within the aforementioned range, it is easier to obtain ultrafine graphene with lower particle size, smaller thickness, higher carbon content and higher yield; when the grinding time is too long (more than 5 hours) or too short (less than 4 hours), it is not conducive to obtaining ultrafine graphene with better particle size and thickness, and the carbon content and yield will also be reduced.
[0031] The speed is controlled at 260rpm~350rpm, and can be selected as 260rpm~300rpm or 300rpm~350rpm, etc.
[0032] In step 1) of the present invention, beating is performed by adding a dispersant and a protective agent. The dispersant is selected from a surfactant, ethanol, etc.; the protective agent is selected from ethanol, ethylene glycol, etc.
[0033] In step 1) of the present invention, separation: using a filter press to separate the graphite powder, and drying the graphite powder using a flash evaporation device. The drying temperature can be, for example, 300°C to 400°C. It can be 300°C to 350°C or 350°C to 400°C.
[0034] In step 1) of the present invention, low temperature ball milling: the dried graphite powder is put into a liquid nitrogen ball mill for ball milling.
[0035] The ball-to-material ratio is 9:1-7:1, and can be selected as 9:1-8:1 or 8:1-7:1, etc.
[0036] The ball milling time is 2 to 3 hours, and can be selected as 2 to 2.5 hours or 2.5 to 3 hours.
[0037] The speed is controlled at 800rpm~1200rpm, and can be selected as 800rpm~1000rpm or 1000rpm~1200rpm, etc.
[0038] The ball milling temperature is -50°C to -60°C, and can be selected as -50°C to -55°C or -55°C to -60°C, etc.
[0039] Grinding graphite flakes in a low temperature environment increases the brittleness of graphite, opens the graphite lattice structure, and promotes subsequent oxidant penetration and oxidation. When the ball milling temperature is too high, it is not conducive to obtaining ultrafine graphene with better particle size and thickness.
[0040] In the preparation method of ultrafine graphene provided by the present invention, step 2) is stepwise oxidation, including pre-oxidation, primary oxidation, adding auxiliary agent (intercalation agent) to assist oxidation intercalation, secondary oxidation, and filter pressing after secondary oxidation. Specifically, oxidant 1 and ultrafine graphite powder provided in step 1) are sequentially added to a reactor and stirred and mixed for pre-oxidation; oxidant 2 is added to the reactor and stirred continuously for primary oxidation; intercalation agent is added to the reactor and stirred continuously for assisting oxidation intercalation; oxidant 2 is added to the reactor and stirred continuously for secondary oxidation; filter pressing is used to provide materials and filter out waste acid.
[0041] In the pre-oxidation step of step 2) of the present invention, the oxidant 1 is selected from perchloric acid. The oxidant 1 is perchloric acid, which is unexpectedly discovered through experiments. When the oxidant 1 is sulfuric acid, the thickness of the obtained graphene is greater than that of perchloric acid.
[0042] In the pre-oxidation step of step 2) of the present invention, the mass ratio of the oxidant 1 to the ultrafine graphite powder is 2.3:1-1.7:1, which can be 2.3:1-2:1 or 2:1-1.7:1, etc. Within the aforementioned range, it is easier to obtain ultrafine graphene with smaller thickness, higher carbon content and yield; when the mass ratio in the pre-oxidation step increases (for example, greater than 2.3:1), the thickness of the graphene increases, and the carbon content and yield are relatively low.
[0043] In the pre-oxidation step of step 2) of the present invention, the reaction temperature of the pre-oxidation is 20°C to 40°C, which can be 20°C to 30°C or 30°C to 40°C, etc. The reaction time of the pre-oxidation is 15min to 25min, which can be 15min to 20min or 20min to 25min, etc. If the pre-oxidation time is too long, it will lead to excessive oxidation of graphite, detachment of interlayer compounds, etc., which is not conducive to the expansion of oxidized graphite and the difficulty of subsequent sheet peeling; if the pre-oxidation time is short, the graphite is not fully oxidized, the interlayer bonding force is still large, which is not conducive to intercalation, and the final product is thicker.
[0044] In the primary oxidation step of step 2) of the present invention, the oxidant 2 is selected from one or both of potassium permanganate and nitric acid. The oxidant 2 accounts for 2.8% to 3.2% of the total mass of graphite and the oxidant 1, which can be 2.8% to 3.0% or 3.0% to 3.2%. The reaction temperature of the primary oxidation is 20°C to 40°C, which can be 20°C to 30°C or 30°C to 40°C. The reaction time of the primary oxidation is 25 to 35 minutes, which can be 25 to 30 minutes or 30 to 35 minutes.
[0045] In step 2) of the present invention, the intercalant is selected from one or more of ammonium nitrate, glacial acetic acid, and propionic acid. The intercalant accounts for 1.8% to 2.2% of the total mass of graphite and oxidant 1; it can be 1.8% to 2.0% or 2.0% to 2.2%, etc. The reaction temperature is 20°C to 40°C, and can be 20°C to 30°C or 30°C to 40°C, etc. The reaction time is 14min to 16min, and can be 14min to 15min or 15min to 16min, etc.
[0046] In step 2) of the present invention, in the secondary oxidation, the oxidant 2 is selected from one or both of potassium permanganate and nitric acid. The oxidant 2 accounts for 1.8% to 2.2% of the total mass of graphite and the oxidant 1, which can be 1.8% to 2.0% or 2.0% to 2.2%. The reaction temperature of the secondary oxidation is 35°C to 40°C, which can be 35°C to 38°C or 38°C to 40°C. The reaction time of the secondary oxidation is 30min to 40min, which can be 30min to 35min or 35min to 40min.
[0047] Preferably, in the secondary oxidation, oxidant 2 is added in 5 to 7 times. It is easier to obtain graphene with a smaller thickness by adding oxidant 2 in batches than by adding it all at once, and the carbon content of oxidant 2 added in batches is better than that of adding it all at once. The thickness of graphene without secondary oxidation is much higher than that of graphene after secondary oxidation, and the carbon content is lower than that of graphene after secondary oxidation. The interval time of adding oxidant 2 in batches is 6 to 7 minutes. If the interval time of adding oxidant 2 in batches is too long or too short, the reaction will be too intense if it is too short, and the reaction time will be extended in disguise if it is too long, which will also affect the thickness of graphene. If the interval time is within the above range, ultrafine graphene with a smaller thickness can be obtained.
[0048] Combined with the secondary oxidation process, the degree of reaction can be effectively controlled, a larger expansion ratio can be obtained, the intercalation effect can be guaranteed, the subsequent stripping can be more thorough, and the ultrafine graphene obtained can be of higher purity.
[0049] In step 2) of the present invention, waste acid is filtered out using a filter press, and the waste acid is treated in a sewage treatment workshop. The waste acid generated by the initial filter press can be recycled.
[0050] In the method for preparing ultrafine graphene provided by the present invention, step 3) is microwave and other treatments, including high-temperature microwave, ultrasound, filter pressing, and drying. Specifically, the material provided in step 2) is microwave-treated to provide expanded graphite powder; the expanded graphite powder is mixed with a solvent, subjected to ultrasound, filter pressing, and drying to obtain ultrafine graphene.
[0051] In the microwave step of step 3) of the present invention, the material enters a microwave tunnel kiln and is treated at 900-1000° C. for 0.5-1 min to obtain expanded graphite powder. Optionally, the microwave treatment temperature is 900-950° C. or 950-1000° C., and the microwave treatment time is 0.5-0.8 min or 0.8-1.0 min, etc.
[0052] In the ultrasonic step of step 3) of the present invention, the solvent is selected from N,N-dimethylformamide and water; the volume ratio of N,N-dimethylformamide and water is 10:1 to 11:1. Optionally, the volume ratio of N,N-dimethylformamide and water is 10:1 to 10.5:1 or 10.5:1 to 11:1, etc. The solid content of the expanded graphene after mixing with the solvent is 1% to 2%, which can be 1% to 1.5% or 1.5% to 2%, etc. The ultrasonic conditions include: the temperature is 35°C to 45°C, which can be 35°C to 40°C or 40°C to 45°C, etc. The frequency is 10Khz to 30Khz, which can be 10Khz to 20Khz or 20Khz to 30Khz, etc. The ultrasonic time can be, for example, 2 to 4 hours, which can be 2 to 3 hours or 3 to 4 hours, etc.
[0053] In the filter pressing and drying step of step 3) of the present invention, the graphene is separated by using a filter press, and the graphene is dried by using a flash evaporation device at 300° C. to 400° C. The drying temperature can be selected from 300° C. to 350° C. or 350° C. to 400° C., etc.
[0054] Ultrafine graphene
[0055] The present invention also provides an ultrafine graphene, which is prepared by the method for preparing ultrafine graphene provided by the first aspect of the present invention. The nanoscale super graphene material prepared by the present invention has uniform size, high carbon content, small thickness, small particle size and high yield. Specifically:
[0056] In the ultrafine graphene provided by the present invention, the carbon content of the ultrafine graphene is above 96%, for example, up to 97.5%. It can be selected from 96% to 97.5%, 96% to 97.2%, 96% to 97.3%, 96% to 97%, 96% to 97.4%, 96% to 97.6%, 96% to 97.1%, 96% to 97.3%, 96% to 96.7%, etc.
[0057] In the ultrafine graphene provided by the present invention, the thickness of the ultrafine graphene is 0.5nm-0.8nm, which can be selected from 0.5nm-0.7nm, 0.5nm-0.6nm, 0.6nm-0.7nm, 0.7nm-0.8nm, 0.5nm-0.65nm, 0.65nm-0.8nm, 0.5nm-0.67nm, 0.67nm-0.8nm, 0.5nm-0.68nm, 0.68nm-0.8nm, 0.5nm-0.62nm, 0.62nm-0.8nm, 0.5nm-0.63nm, 0.63nm-0.8nm, 0.5nm-0.66nm or 0.66nm-0.8nm, etc.
[0058] In the ultrafine graphene provided by the present invention, the particle size D50 of the ultrafine graphene is 0.4 μm to 0.5 μm, which can be 0.4 μm to 0.41 μm, 0.41 μm to 0.5 μm, 0.44 μm to 0.44 μm, 0.4 μm to 0.45 μm, 0.45 μm to 0.5 μm, 0.4 μm to 0.42 μm or 0.42 μm to 0.5 μm, etc.
[0059] In the ultrafine graphene provided by the present invention, the yield of the ultrafine graphene can be as high as 98% to 99%.
[0060] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is described in detail below in conjunction with embodiments and drawings.
[0061] In the following examples, unless otherwise specified, all reaction raw materials are commercially available products.
[0062] Unless otherwise specified, the purity of each product in each embodiment of the present invention exceeds 98%.
[0063] Example 1
[0064] 100 kg of high carbon flake graphite was selected as raw material (C%: 96, 100 mesh) for processing.
[0065] (1) Crushing: Grind using a stirred ball mill (ZJM-20) with a ball-to-material ratio of 10:1, add 25% ethanol to the graphite for slurrying, grind for 4.5 hours, and rotate at 300 rpm; separate the graphite powder using a filter press, and dry the graphite powder at 340°C using a flash evaporator.
[0066] (2) Low temperature ball milling: liquid nitrogen ball mill ball to material ratio 8:1, grinding time 2.5 hours; rotation speed 1000 rpm, grinding temperature -60 °C.
[0067] (3) Pre-oxidation: 200 kg of perchloric acid and ultrafine graphite powder were added to the reactor in a mass ratio of 2:1 and stirred. The reaction temperature was 40°C and the reaction time was 20 min.
[0068] (4) Primary oxidation: Add 9 kg of potassium permanganate and continue stirring. The reaction temperature is 30° C. and the reaction time is 30 min.
[0069] (5) Adding auxiliary agent: Add 6 kg of ammonium nitrate to assist oxidation intercalation, and stir at a constant temperature of 30° C. for 15 min.
[0070] (6) Secondary oxidation: 6 kg of potassium permanganate was added to the reactor in five times, with an interval of 7 min between each time, and stirring was continued. The reaction temperature was 30° C. and the reaction time of this step was 35 min in total.
[0071] (7) Filter pressing: Use a filter press to filter out the waste acid, and the waste acid is sent to the sewage treatment workshop for treatment;
[0072] (8) High-temperature microwave treatment: After filtration, the material enters a microwave tunnel kiln and is treated at 950°C for 1 min to obtain expanded graphite powder.
[0073] (9) Ultrasound: Expanded graphite and N,N-dimethylformamide / water (10.5:1) solution were mixed and added into an ultrasonic reactor, with a solid content of 1.2% after mixing. Ultrasound was carried out at 40°C and 20Khz for 3 hours.
[0074] (10) Filter pressing and drying: Graphene is separated using a filter press and then dried at 340 °C using a flash evaporation device.
[0075] Laser particle size analyzer and AFM analysis showed that the product particle size (D50) was 0.41 μm, thickness was 0.6 nm, carbon content was 97.5%, and yield was 98.5%.
[0076] Example 2
[0077] The preparation process is basically the same as that in Example 1, except that the ball-to-material ratio in step (1) is replaced with 11:1.
[0078] Example 3
[0079] The preparation process is basically the same as that in Example 1, except that the ball-to-material ratio in step (1) is replaced with 9:1.
[0080] Example 4
[0081] The preparation process is basically the same as that in Example 1, except that the ball milling time in step (1) is replaced with 5 hours.
[0082] Example 5
[0083] The preparation process is basically the same as that in Example 1, except that the ball milling time in step (1) is replaced with 4 hours.
[0084] Comparative Example 1
[0085] The preparation process is basically the same as that of Example 1, except that the ball milling time in step (1) is replaced with 6 hours.
[0086] Comparative Example 2
[0087] The preparation process is basically the same as that of Example 1, except that the ball milling time in step (1) is replaced with 3 hours.
[0088] Example 6
[0089] The preparation process is basically the same as that in Example 1, except that the ball milling temperature in step (2) is replaced with -50°C.
[0090] Comparative Example 3
[0091] The preparation process is basically the same as that of Example 1, except that the ball milling temperature in step (2) is replaced with 120°C.
[0092] Comparative Example 4
[0093] The preparation process is basically the same as that of Example 1, except that the oxidant in step (3) is replaced by sulfuric acid.
[0094] Example 7
[0095] The preparation process is basically the same as that in Example 1, except that the material ratio in step (3) is replaced with 2.3:1.
[0096] Example 8
[0097] The preparation process is basically the same as that in Example 1, except that the material ratio in step (3) is replaced with 1.7:1.
[0098] Comparative Example 5
[0099] The preparation process is basically the same as that of Example 1, except that the material ratio in step (3) is replaced with 3:2.
[0100] Comparative Example 6
[0101] The preparation process is basically the same as that of Example 1, except that the material ratio in step (3) is replaced with 5:2.
[0102] Example 9
[0103] The preparation process is basically the same as that in Example 1, except that the pre-oxidation time in step (3) is replaced with 25 min.
[0104] Example 10
[0105] The preparation process is basically the same as that in Example 1, except that the pre-oxidation time in step (3) is replaced with 15 minutes.
[0106] Comparative Example 7
[0107] The preparation process is basically the same as that of Example 1, except that the pre-oxidation time in step (3) is replaced with 40 minutes.
[0108] Comparative Example 8
[0109] The preparation process is basically the same as that in Example 1, except that the pre-oxidation time in step (3) is replaced with 20 min.
[0110] Embodiment 11
[0111] The preparation process is basically the same as that in Example 1, except that the intercalant in step (5) is replaced by propionic acid.
[0112] Comparative Example 9
[0113] The preparation process is basically the same as that of Example 1, except that potassium permanganate is added in one go in step (6).
[0114] Comparative Example 10
[0115] The preparation process is basically the same as that of Example 1, except that step (6) is removed.
[0116] Comparative Example 11
[0117] The preparation process is basically the same as that in Example 1, except that the interval time in step (6) is replaced with 8 minutes.
[0118] Comparative Example 12
[0119] The preparation process is basically the same as that in Example 1, except that the interval time in step (6) is replaced with 3 minutes.
[0120] Table 1
[0121]
[0122]
[0123] From Table 1, we can see that:
[0124] In combination with Examples 1 to 11, the particle size D50 of the ultrafine graphene is 0.4 μm to 0.45 μm, the thickness of the ultrafine graphene is 0.5 nm to 0.8 nm, the carbon content of the ultrafine graphene is more than 96%, and the yield of the ultrafine graphene can be as high as 98% to 99%.
[0125] In combination with Example 1 and Comparative Example 1, when the ball milling time in the crushing step (1) is increased to 6 hours, the thickness of the graphene is 0.81 nm, which is much larger than the thickness of the graphene in Example 1, and the carbon content and yield are not as good as those in Example 1; in combination with Example 1 and Comparative Example 2, when the ball milling time in the crushing step (1) is reduced to 3 hours, the thickness of the graphene is 0.94 nm, and the particle size D50 is 0.9 μm, which is much larger than that in Example 1 in terms of both particle size and thickness, and the carbon content is not as good as that in Example 1. Therefore, the grinding time in the crushing step has a great influence on the acquisition of ultrafine graphene.
[0126] In combination with Example 1 and Comparative Example 3, when the ball milling temperature in step (2) of low-temperature ball milling is replaced with 120°C, the thickness of graphene is 0.95nm and the particle size D50 is 0.88μm, both of which are much larger than those in Example 1. Therefore, it is better to use low-temperature ball milling.
[0127] In combination with Example 1 and Comparative Example 4, when the pre-oxidation oxidant in step (3) is sulfuric acid, the thickness of the graphene is 0.99 nm, which is much higher than 0.6 nm in Example 1. Therefore, the effect of using perchloric acid as the pre-oxidation oxidant is significantly better than that of using sulfuric acid.
[0128] In combination with Example 1 and Comparative Examples 5 and 6, when the mass ratio in the pre-oxidation step of step (3) increases, the thickness of the graphene is greater than that of Example 1, especially in Comparative Example 5, the carbon content and yield are not as high as those of Example 1. The mass ratio of the pre-oxidation step should also be within the appropriate range defined in the present invention.
[0129] In combination with Example 1 and Comparative Example 7, the pre-oxidation time is too long, resulting in excessive oxidation of graphite, detachment of interlayer compounds, etc., which is not conducive to the expansion of oxidized graphite and makes subsequent layer peeling difficult. The thickness of the obtained graphene is 0.85 mm, which is much higher than that of Example 1.
[0130] Combining Example 1 and Comparative Example 8, the pre-oxidation time is short, the graphite oxidation is not sufficient, the interlayer bonding force is still large, which is not conducive to intercalation, and the final product is thicker. The thickness of the obtained graphene is 0.89 mm, which is much higher than that of Example 1.
[0131] In combination with Example 1 and Comparative Example 9, it is easier to obtain graphene with a smaller thickness by adding potassium permanganate in batches than by adding it all at once.
[0132] In combination with Example 1 and Comparative Example 10, the thickness of the graphene that has not undergone secondary oxidation is much higher than the thickness of the graphene that has undergone secondary oxidation, and the carbon content is lower than that of the graphene that has undergone secondary oxidation.
[0133] In combination with Example 1, Comparative Example 11 and Comparative Example 12, the interval time for adding in batches is too long or too short. If it is too short, the reaction is too intense, while if it is too long, the reaction time is extended in disguise, which has a greater impact on the thickness of graphene.
[0134] The above-mentioned embodiments are preferred examples of the present invention and are not intended to limit the protection scope of the present invention.
[0135] The applicant declares that the present invention illustrates the method for preparing ultrafine graphene of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
[0136] The above embodiments are preferred cases of the present invention and are not intended to limit the protection scope of the present invention. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention.
[0137] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A method for preparing ultrafine graphene, characterized in that: The preparation method comprises the following steps: 1) Crushing and low temperature ball milling: Crushing and low temperature ball milling of graphite to provide ultrafine graphite powder; 2) Stepwise oxidation: mixing oxidant 1 with the ultrafine graphite powder provided in step 1) for pre-oxidation; adding oxidant 2 for primary oxidation; adding intercalation agent for auxiliary oxidation intercalation; adding oxidant 2 for secondary oxidation; filtering to provide material and filter out waste acid; 3) Microwave and other treatments: microwave the material provided in step 2) to provide expanded graphite powder; mix the expanded graphite powder with a solvent, perform ultrasonic treatment, filter pressing, and dry to obtain ultrafine graphene; In step 1), the ball milling time is 2 to 3 hours, and the ball milling temperature is -50°C to -60°C; Step 2) In the pre-oxidation, the oxidant 1 is selected from perchloric acid; the mass ratio of the oxidant 1 to the ultrafine graphite powder is 2.3:1 to 1.7:1; in the secondary oxidation, the oxidant 2 is added 5 to 7 times with an interval of 6 min to 7 min; The reaction temperature of the pre-oxidation is 20°C to 40°C; the reaction time of the pre-oxidation is 15 min to 25 min; the oxidant 2 is selected from one or two of potassium permanganate and nitric acid; in the primary oxidation, the oxidant 2 accounts for 2.8% to 3.2% of the total mass of graphite and oxidant 1; the reaction temperature of the primary oxidation is 20°C to 40°C; the reaction time of the primary oxidation is 25 min to 35 min; the intercalation agent is selected from one or more of ammonium nitrate, glacial acetic acid, and propionic acid; the intercalation agent accounts for 1.8% to 2.2% of the total mass of graphite and oxidant 1; the reaction temperature is 20°C to 40°C, and the reaction time is 14 min to 16 min; in the secondary oxidation, the oxidant 2 accounts for 1.8% to 2.2% of the total mass of graphite and oxidant 1; the reaction temperature of the secondary oxidation is 35°C to 40°C; the reaction time of the secondary oxidation is 30 min to 40 min; The microwave treatment temperature is 900-1000° C.; the microwave treatment time is 0.5-1 min.
2. The method for preparing ultrafine graphene according to claim 1, characterized in that: In step 1), the graphite is ground, pulped, separated, and dried to provide dried graphite powder, and the dried graphite powder is low-temperature ball-milled to provide ultrafine graphite powder.
3. The method for preparing ultrafine graphene according to claim 2, characterized in that: Also includes one or more of the following features: A1) the graphite is flake graphite, and the particle size N of the flake graphite is 100 mesh>N>325 mesh; A2) Grinding graphite using a ball mill; A3) the grinding medium is selected from high chromium steel balls or zirconium oxide balls; A4) Beating by adding dispersant and protective agent; A5) Use a filter press to separate the graphite powder, and use a flash evaporation device to dry the graphite powder; A6) The dried graphite powder is put into a liquid nitrogen ball mill for ball milling.
4. The method for preparing ultrafine graphene according to claim 3, characterized in that: Also includes one or more of the following features: A21) In A2), the ball to material ratio is 11:1~9:1, the grinding time is 4~5 hours, and the rotation speed is controlled at 260 rpm ~350rpm; A61) In A6), the ball-to-material ratio is 9:1 ~ 7:1, the ball milling time is 2 ~ 3 hours, the rotation speed is controlled at 800 rpm ~1200 rpm, and the ball milling temperature is -50℃ ~ -60℃.
5. The method for preparing ultrafine graphene according to claim 1, characterized in that: In step 2), the waste acid is treated in a sewage treatment workshop; and / or the waste acid generated by the initial filter press is recycled.
6. The method for preparing ultrafine graphene according to claim 1, characterized in that: In step 3), the material enters a microwave tunnel kiln.
7. The method for preparing ultrafine graphene according to claim 1, characterized in that: In step 3), any one or more of the following features are also included: D1) the solvent is selected from N,N-dimethylformamide and water; the volume ratio of N,N-dimethylformamide to water is 10:1 to 11:1; D2) the solid content of the expanded graphene after mixing with the solvent is 1% to 2%; D3) the ultrasonic temperature is 35°C to 45°C; D4) The frequency of the ultrasound is 10 Khz ~ 30 Khz; D5) Separate the graphene using a filter press and dry the graphene using a flash evaporation device at 300°C to 400°C.
Citation Information
Patent Citations
Concentrated water dispersion of graphene and method for the preparation thereof
CN105073636A
Preparation method and application of graphene powder
CN111559743A